Characterizing the influence of gut microbiota on host tryptophan metabolism with germ-free pigs - Bingnan Liu; Dongming Yu; Jing Sun; Xiaoyan Wu; Zhongquan Xin; Baichuan Deng; Lijuan Fan; Jian Fu; Liangpeng Ge; Wenkai Ren (Animal Nutrition, 2022)
Intestinal microbes are closely associated with host health, depending on metabolic crosstalk between the microbiota and host. Tryptophan metabolism is one of the best examples of metabolic crosstalk between intestinal microbiota and host; however, our understanding about the influence of intestinal microbiota on host tryptophan metabolism is limited. Thus, we established germ-free (GF) pig models to systemically explore the influence of intestinal microbiota on tryptophan metabolism. Five GF pigs were kept in GF conditions throughout the experiment (GF group). Six GF pigs were transplanted with fecal microbiota from donor sows to act as control pigs. Compared with control pigs, the GF pigs had remarkable alterations in tryptophan metabolism. The differential metabolites (P < 0.05) were mainly found in the liver, circulation system and large intestine. Notably, the alteration of metabolites in tryptophan metabolism varied among organs, especially for the serotonin pathway. In GF pigs, tryptophan and kynurenine in the large intestine and 5-hydroxytryptophan in most organs were increased (P < 0.05), while metabolites in the indole pathway in most organs were decreased (P < 0.05). Collectively, our study reveals changes in tryptophan metabolism in GF pigs, highlighting the critical role of gut microbes in shaping host tryptophan metabolism.